Life Cycle of the Parasite Profilicollis chasmagnathi (Acanthocephala) on the Patagonian Coast of Argentina Based on Morphological and Molecular Data - Lorenti, Eliana Andrea (2018)
This study verifies the identity of adult specimens of the parasite Profilicollis chasmagnathi (Acanthocephala, Polymorphidae) recovered from kelp gulls Larus dominicanus (Aves, Laridae), and cystacanths found in crabs Cyrtograpsus altimanus (Crustacea, Decapoda) from the southwestern Atlantic coast. The life cycle of this parasite is elucidated in the intertidal zone of Patagonia, Argentina, based on morphological and molecular data. Preferences by size and sex of the intermediate host and seasonal variation of this parasite are provided, contributing to the knowledge of this host-parasite association.